Virulome and genome analyses identify associations between antimicrobial resistance genes and virulence factors in highly drug-resistant Escherichia coli isolated from veal calves - Bradd J. Haley; Seon Woo Kim; Serajus Salaheen; Ernest Hovingh; Jo Ann S. Van Kessel (PLoS ONE, 2022)
Food animals are known reservoirs of multidrug-resistant (MDR) Escherichia coli, but information regarding the factors influencing colonization by these organisms is lacking. Here we report the genomic analysis of 66 MDR E. coli isolates from non-redundant veal calf fecal samples. Genes conferring resistance to aminoglycosides, β-lactams, sulfonamides, and tetracyclines were the most frequent antimicrobial resistance genes (ARGs) detected and included those that confer resistance to clinically significant antibiotics (blaCMY-2, blaCTX-M, mph(A), erm(B), aac(6’)Ib-cr, and qnrS1). Co-occurrence analyses indicated that multiple ARGs significantly co-occurred with each other, and with metal and biocide resistance genes (MRGs and BRGs). Genomic analysis also indicated that the MDR E. coli isolated from veal calves were highly diverse. The most frequently detected genotype was phylogroup A-ST Cplx 10. A high percentage of isolates (50%) were identified as sequence types that are the causative agents of extra-intestinal infections (ExPECs), such as ST69, ST410, ST117, ST88, ST617, ST648, ST10, ST58, and ST167, and an appreciable number of these isolates encoded virulence factors involved in the colonization and infection of the human urinary tract. There was a significant difference in the presence of multiple accessory virulence factors (VFs) between MDR and susceptible strains. VFs associated with enterohemorrhagic infections, such as stx, tir, and eae, were more likely to be harbored by antimicrobial-susceptible strains, while factors associated with extraintestinal infections such as the sit system, aerobactin, and pap fimbriae genes were more likely to be encoded in resistant strains. A comparative analysis of SNPs between strains indicated that several closely related strains were recovered from animals on different farms indicating the potential for resistant strains to circulate among farms. These results indicate that veal calves are a reservoir for a diverse group of MDR E. coli that harbor various resistance genes and virulence factors associated with human infections. Evidence of co-occurrence of ARGs with MRGs, BRGs, and iron-scavenging genes (sit and aerobactin) may lead to management strategies for reducing colonization of resistant bacteria in the calf gut.